Parasite dynamics in the peripheral blood and the placenta during pregnancy-associated malaria infection. (December 2016) - Cohee, Lauren; Kalilani-Phiri, Linda; Mawindo, Patricia; Joshi, Sudhaunshu; Adams, Matthew; Kenefic, Leo; Jacob, Christopher; Taylor, Terrie; Laufer, Miriam
Abstract Background Malaria infections during pregnancy lead to sequestration of parasite infected red blood cells in the placenta. Placental infection can result in adverse outcomes for mothers and infants. Despite many studies, it remains unclear which peripheral blood infections during pregnancy lead to development of placental malaria. Understanding the timing of peripheral infections that lead to placental malaria and the ability of intermittent preventive treatment with sulfadoxine–pyrimethamine (SP-IPT) and artemisinin-based combination therapy to clear infections will enable the rational design of new interventions to decrease the burden of malaria in pregnancy. Methods Microsatellite markers were used to genotype peripheral and placental malaria infections in an observational cohort in Blantyre, Malawi. Genotypes were compared to determine the timing of infections that sequester in the placenta. The effects of SP-IPT and artemether–lumefantrine as curative treatment were also evaluated by assessing the occurrence of peripheral infections or matching genotypes between peripheral and placental parasites following treatment. Results Genotypes from 92 peripheral samples prior to delivery, 26 peripheral samples at delivery, and 29 placental samples were compared. Thirty percent of women with genotyped parasites in their placentas that had peripheral infections detected during pregnancy had matching peripheral-placental genotypes. Matching genotypes were not associated with gestational age and occurred from 13 to 39 weeks. Among women with more than one genotyped peripheral infection during pregnancy, 80 % had persistent infection with the same genotype while the remaining were new infections. Among infections treated with SP or artemether–lumefantrine, 28/84 (33 %) and 9/56 (16 %) had infection detected after treatment, respectively. Recrudescent infections were detected after both treatments and occurred up to 76 days after treatment. Women treated with SP-IPT and artemether–lumefantrine had genotypes matching treated infections detected in the placenta. Conclusions Placental malaria can occur at any time during pregnancy. In the context of late enrollment in antenatal care, interventions that protect all women of childbearing age and throughout pregnancy are needed. Currently used medications do not always clear peripheral or placental infections. The ability of anti-malarial drugs to prevent or clear placental infections should be considered in the development of future interventions.